2013
DOI: 10.1039/c3cs35440g
|View full text |Cite
|
Sign up to set email alerts
|

Blue fluorescent emitters: design tactics and applications in organic light-emitting diodes

Abstract: Organic light-emitting diodes (OLEDs) are competitive candidates for the next generation flat-panel displays and solid state lighting sources. Efficient blue-emitting materials have been one of the most important prerequisites to kick off the commercialization of OLEDs. This tutorial review focuses on the design of blue fluorescent emitters and their applications in OLEDs. At first, some typical blue fluorescent materials as dopants are briefly introduced. Then nondoped blue emitters of hydrocarbon compounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
429
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 776 publications
(434 citation statements)
references
References 55 publications
(50 reference statements)
2
429
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Blue light-emitting pixels, the key component for full-color displays and high color purity lightening, lags far behind the green-and red-counterparts. [9][10][11] Among the current available blue light-emitting polymers, poly(9,9-dioctylfluorene) (PFO) is one of the most widely used polymers, showing good color purity, high photoluminescent quantum efficiency, excellent processability, and good thermal and electrochemical stability. [12][13][14][15][16][17] It has been shown that PFO is rich in morphology and can form different supramolecular structures such as the -phase, -phase, -phase, and the nematic-phase, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Blue light-emitting pixels, the key component for full-color displays and high color purity lightening, lags far behind the green-and red-counterparts. [9][10][11] Among the current available blue light-emitting polymers, poly(9,9-dioctylfluorene) (PFO) is one of the most widely used polymers, showing good color purity, high photoluminescent quantum efficiency, excellent processability, and good thermal and electrochemical stability. [12][13][14][15][16][17] It has been shown that PFO is rich in morphology and can form different supramolecular structures such as the -phase, -phase, -phase, and the nematic-phase, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most pressing material issue in OLEDs is the bluegap (Fig. 9): In modern, commercial OLEDs, fluorescent materials 92 are used in addition to phosphorescent materials, even though this leads to an increased power consumption. The main reason for this is the unavailability of stable deepblue phosphorescent emitters.…”
Section: Potential Economic Impact Of Thermally Activated Delayedmentioning
confidence: 99%
“…To achieve the wide band gap it is necessary to confine the extent of conjugation imposing constraints in the molecular size or introducing a twist between conjugated rings. This implies the design of non-planar conjugated structures [3]. Despite poly( p -phenylenes) are still the most employed organic materials for short-wavelength emitters, they exhibit poor solubility in organic solvents and they are difficult to process [4].…”
Section: Introductionmentioning
confidence: 99%